PRESERVASI ARSIP KERTAS: EVALUASI PENGGUNAAN MAGNESIUM KARBONAT DAN METIL SELULOSA: Array - Yanah Suryanah; Sari Hasanah; Fitra Yeni (Arsip Nasional Republik Indonesia, 2019)
Damage to archives stored for a long time threatens to reduce the shelf life of archives and their existence in the future. Efforts to conserve the archive are done to reduce the damage that occurs. This study aims to study the effect of the use of Magnesium Carbonate and the effect of the use of Methyl Cellulose in the improvement of the paper-based archives. Acidic archive papers are treated by using Magnesium Carbonate and Bookkeeper solution. The acidity of the paper is tested before and after treatment. In the restoration of the archive using Methyl Cellulose, Japanese tissue was applied using Methyl Cellulose glue on archive paper. The effect of the use of glue was observed from changes in the characteristics of the paper before and after treatment. The parameters tested include grammage, thickness, tear resistance, folding resistance, internal bonding, water absorption, ash content, and acidity. The result showed that Magnesium Carbonate can significantly increase pH but this chemical cannot be used in spraying. Other results show that the improvement of the archive using Methyl Cellulose can increase the strength of the paper but further research is needed to determine its effect after being stored for a long time.